2013
DOI: 10.1007/s00056-013-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetischer Hintergrund nonsyndromaler Oligodontien – ein systematisches Review mit Metaanalyse

Abstract: In order of decreasing frequency, PAX9, EDA, MSX1, AXIN2, EDARADD, NEMO, and KRT17 are the seven genes currently known to have a potential for causing nonsyndromic oligodontia. TAC scores enabled us to identify an association between oligodontia phenotypes and genotypes in the patients covered by this meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 73 publications
0
24
0
6
Order By: Relevance
“…Those studies indicated the genes, such as PAX9, EDA, MSX1, AXIN2, EDARADD, NEMO, and KRT17 (Ruf et al, 2013), that affect tooth formation. However, mutations of these genes are not related to the prevalence of CL/P, and there is a difference in the distribution and prevalence of hypodontia between the subjects with and without CL/P.…”
mentioning
confidence: 97%
“…Those studies indicated the genes, such as PAX9, EDA, MSX1, AXIN2, EDARADD, NEMO, and KRT17 (Ruf et al, 2013), that affect tooth formation. However, mutations of these genes are not related to the prevalence of CL/P, and there is a difference in the distribution and prevalence of hypodontia between the subjects with and without CL/P.…”
mentioning
confidence: 97%
“…Earlier, mutations in the PAX9 gene had been identified in association with oligodontia in a family affected with agenesis of most of the permanent molars and a variable absence of second premolars and mandibular incisors (20). Patients with PAX9 gene mutations have not been reported to have an increased risk of syndromic diseases or abnormalities other than oligodontia (21). In addition, PAWLOWSKA et al (22) sequenced fragments of the PAX9 gene in 38 individuals with different types of tooth agenesis and in 100 controls.…”
Section: Pax9 Mutation In Oligodontiamentioning
confidence: 99%
“…As genetic factors have been identified as the major etiology of tooth agenesis, variants in several genes have been reported to be associated with STA, including PAX9 (paired box gene 9), MSX1 (muscle segment homeobox 1), AXIN2 (axis inhibition protein 2), WNT10A (wingless‐type MMTV integration site family, member 10A), WNT10B (wingless‐type MMTV integration site family, member 10B), EDA (ectodysplasin‐A), EDARADD (edar‐associated death domain), LRP 6 (low‐density lipoprotein receptor‐related protein 6), and LTBP3 (latent TGF‐b‐binding protein 3). (Bergendal, Klar, Stecksén‐Blicks, Norderyd, & Dahl, ; Lammi et al, ; Massink et al, ; Noor et al, ; Ruf, Klimas, Honemann, & Jabir, ; Song et al, ; Stockton, Das, Goldenberg, D'Souza, & Patel, ; Vastardis, Karimbux, Guthua, Seidman, & Seidman, ; Wong et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%